2012
DOI: 10.1242/bio.20123160
|View full text |Cite
|
Sign up to set email alerts
|

In vivo genetic manipulation of cortical progenitors in gyrencephalic carnivores using in utero electroporation

Abstract: SummaryBrain structures such as the outer subventricular zone (OSVZ) and the inner fiber layer (IFL) in the developing cerebral cortex are especially prominent in higher mammals. However, the molecular mechanisms underlying the formation of the OSVZ are still largely unknown, mainly because genetic manipulations that can be applied to the OSVZ in higher mammals had been poorly available. Here we developed and validated a rapid and efficient genetic manipulation technique for germinal zones including the OSVZ u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 42 publications
2
68
0
Order By: Relevance
“…These insights are complemented, on the one hand, by advances in novel transgenic, primate and non-primate, animal models, such as the gyrencephalic ferret [95], the marmoset [96] or the macaque [97]. On the other hand, 3D cerebral organoids generated from human and non-human primate iPSCs provide promising tools to dissect evolutionary differences in cortical development in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…These insights are complemented, on the one hand, by advances in novel transgenic, primate and non-primate, animal models, such as the gyrencephalic ferret [95], the marmoset [96] or the macaque [97]. On the other hand, 3D cerebral organoids generated from human and non-human primate iPSCs provide promising tools to dissect evolutionary differences in cortical development in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…We performed IUE of ferret embryos to deliver the DN-YAP construct into the developing ferret neocortex (Kawasaki et al, 2012;Kawasaki et al, 2013). Specifically, we coelectroporated the ferret dorsolateral neocortex with either CAGGS-empty vector plus CAGGS-EGFP or with CAGGS-DN-YAP plus CAGGS-EGFP.…”
Section: Dominant-negative Yap Expression Reduces Mitotic Bp Abundancmentioning
confidence: 99%
“…In utero electroporation of E33 ferret embryos was performed as originally established (Kawasaki et al, 2012;Kawasaki et al, 2013), with the modifications indicated below.…”
Section: In Utero Electroporation Of Ferretsmentioning
confidence: 99%
“…Electroporation allows for genetic manipulation of neural stem and progenitors cells in a relatively short time window and is therefore less time consuming than transgenesis [4][5][6] . In addition, electroporation of the developing neural tube is very versatile: it can be adapted to different species (mouse, rat and ferret [7][8][9] ) and allows for different types of manipulation, ranging from overexpression of a specific gene to gene knockdown 5 . As electroporation relies on the application of an electric field, only charged molecules can be delivered, thus limiting the spectrum of molecules that can be used.…”
Section: Introductionmentioning
confidence: 99%